It takes a village: how nonprofit leaders work with communities to create social change in Nigeria - Ekwerike, Onyedika (Kansas State University, 2021)
Nigeria is a country blessed with enormous natural resources, yet its citizens suffer chronic poverty. If you walk down any street in Nigeria and ask the people why poverty exists despite all of the country’s resources, you’ll hear two things, bad leadership, and corruption. There seems to be a consensus even in the existing literature that leadership in Nigeria is lacking, and leadership is crucial in overturning the nation’s fortunes. However, scholars argue that a specific kind of leadership is required, a kind of leadership that is rooted in our African culture and values. Many young people have responded to this call for leadership by being civically engaged. Working through nonprofit organizations, these young people are mobilizing resources and engaging communities to create social change. But how do they do it? What is the process? This study answers the question: how do nonprofit leaders in Nigeria work with communities to create social change? Guided by postcolonialism and social change leadership framework, I utilized a qualitative case study method to understand how nonprofit leaders work with communities to create social change. Six executive members of the Mentally Aware Nigeria Initiative (MANI) participated in this study. I collected data through interviews, organizational documents, and a collaborative google document. Data collected was analyzed using abductive thematic analysis. The findings revealed four themes: Leadership expressed as positional authority, Need for leadership as a collective process, Social change leadership activities, and Cultural barriers to engagement. These four themes inform the overarching theme: Nonprofit leaders work with multiple stakeholders to engage in social change activities to create change in their communities. These findings suggest that collaboration is central to the work of leading change. Nonprofit leaders collaborate with multiple stakeholders to offer mental health services, raise awareness, and advocate for policy change. This collaborative approach to leadership is consistent with African values and principles like Ubuntu. However, there are cultural barriers to engagement that leaders must navigate. A key recommendation is that practitioners continue to identify and engage diverse stakeholders to progress on their communities’ challenges. Leadership requires a collective effort, and leadership educators must teach leadership as a collaborative process. Finally, future research should explore culturally relevant practices that foster collaboration.
Keywords: Leadership; Social change; Community engagement; Nonprofit; Mental health; Postcolonialism; Organizational communication; Nigeria; African leadership